A Phenomenological Study of Rural School Consolidation - Keith A. Nita; Marc J. Holley; Sharon L. Wrobel (Journal of Research in Rural Education, 2010)
This study is an investigation of how school consolidation between 2003 and 2006 affected the lived experience of students and educators in four Arkansas high schools. We present findings from twenty-three interviews with students, teachers, and school administrators who moved to a new high school because of consolidation, as well as those who were already in the receiving schools. While educators' and students' lived experiences were diverse and sometimes contradictory, two themes emerged in the interviews. Because of the study design, these findings cannot be generalized to all consolidation contexts, but they were common across the four consolidations studied. First, students adapted better than teachers to the social disruption created by consolidation; teachers struggled with new relationships, both with other teachers and students. Facing the same social disruption, students described more successful transitions. Educators and students alike explained that because "kids are kids," initial tensions tended to resolve themselves eventually. The second theme that emerged from our interviews was that nearly all students and all teachers, moving and receiving, reported experiencing at least some benefits from consolidation. Students experienced broader course offerings and more diverse social opportunities. Teachers had fewer courses to prepare and better professional development opportunities. However, moving teachers and students experienced special challenges. Although students described a "blended" community after consolidation, moving students typically reported having greater challenges fitting in. Finally, the consolidation experience tended to be most difficult for moving teachers.